ANALISIS MORFO-SEMANTIS NAMA-NAMA CAMILAN TRADISIONAL BERKORELASI DENGAN SIFAT DAN BAGIAN TUBUH DI DAERAH ISTIMEWA YOGYAKARTA - , RIZKY PRASETYO AJI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Traditional food is one of the cultural works. According to its function, the food can be divided into staple food, side dish, snack and kinds of food for special events. Side dish and nibbles are staple food distraction called snack. Snacks are divided into two types namely traditional and modern snacks. Some traditional snacks in Yogyakarta (DIY) is unique, naming the snacks by using the name of characters and parts of the body, such as konthol kejepit, mata kebo, turuk bintul, prawan kenÑs, randha royal, semar mendem and so on. The snacks are classified as traditional snacks that have correlated to the characters and parts of body (CBST). This study is analyzing CBST based on morphological analysis and semantic analysis especially about particular components of meaning. Morphologically, CBST is analyzed by compound words and non-compound words. Semantically, CBST as a particular component of meaning is analyzed based on raw materials, shape, color processing and reference in forming elements of CBST. Keywords: Traditional food, traditional snacks, semantics, morphology